Peer-Tutoring to Foster Spoken Fluency in Computer-Mediated Tasks - Jose Miguel Marenco Dominguez (Universidad de La Sabana, 2018)
Twelve 14-to-15-year-old students participated in this investigation. The participants faced difficulties to speak fluently in an L2 and they evinced different levels of proficiency. Therefore, it was planned to assess the effects of peer tutoring and computer-mediated tasks on students' spoken fluency. Differences among learners were the starting point of this research and, consequently, peer tutoring was the strategy proposed. The benefits from collaborating in small groups are supported by previous studies. Tutors learned by teaching, while tutees had more time for individualized instructions. Along with peer tutoring, oral tasks and computer-mediated instructions ornamented this intervention. Qualitative data from learning logs, video recordings, rubric for assessing spoken fluency and a final semi-structured interview pointed to the effectiveness of this inquiry. The results suggest that learners increased self-confidence, enhanced spoken fluency, and improved the outcomes of tasks. Some of these results are also found in similar local and international investigations. What this paper adds is the use of computer-based conferencing as an additional tool for student- student interaction in distance, as well as the improvement of young learners' spoken fluency at a high school level.